Case report: Multiphenotypic cervical cancer resembling human papillomavirus-related multiphenotypic sinonasal carcinoma - Bao, Xiaoxiao; Chen, Yan; Zhang, Jing; Zhang, Xiaowei (Frontiers in Medicine, 2024)
Human papillomavirus (HPV)-related multiphenotypic sinonasal carcinoma (HMSC) is a biphasic epithelial tumor associated with HPV infection. This rare tumor primarily affects the nasal cavity and paranasal sinuses, with only two cases reported outside these locations to date-one in the breast and one in the vulva. This report presents a case of a tumor resembling an HMSC arising in the cervix. A 69-year-old female patient presented to our hospital with a history of vaginal bleeding lasting for more than a year. The patient tested positive for high-risk HPV. A cervical biopsy revealed high-grade squamous cell carcinoma with invasion. Subsequently, the patient underwent radical hysterectomy for cervical cancer. The postoperative pathological diagnosis, based on histology, immunohistochemistry, and HPV testing, was multiphenotypic cervical carcinoma resembling HMSC. The patient did not receive any adjuvant radiotherapy or chemotherapy postoperatively.Notably, during a year of postoperative follow-up, no recurrence or metastasis was observed.Multiphenotypic cervical carcinoma is a rare tumor that resembles HPV-related multiphenotypic sinonasal carcinoma. These tumors are associated with HPV infection, typically exhibit high-grade histological features, and show a propensity for local progression clinically. Accurate identification of these tumors through their histological characteristics and immunohistochemical staining, followed by confirmation with HPV and molecular genetic testing, is crucial for precise diagnosis, prognostication, and effective management.